C5a Blockade Increases Regulatory T Cell Numbers and Protects Against Microvascular Loss and Epithelial Damage in Mouse Airway Allografts - Khan, Mohammad Afzal; Alanazi, Fatimah; Ahmed, Hala Abdalrahman; Vater, Axel; Assiri, Abdullah Mohammed; Broering, Dieter Clemens (Frontiers in Immunology, 2018)
Microvascular injury during acute rejection has been associated with massive infiltration of CD4+ T effector cells, and the formation of complement products (C3a & C5a). Regulatory T cells (Tregs) are potent immunosuppressors of the adaptive immune system, and have proven sufficient to rescue microvascular impairments. Targeting C5a has been linked with improved microvascular recovery, but its effects on the Treg and T effector balance is less well known. Here, we demonstrate the impact of C5a blockade on Treg induction and microvascular restoration in rejecting mouse airway allografts. BALB/c →C57BL/6 allografts were treated with a C5a-neutralizing L-aptamer (10mg/kg, i.p. at d0 and every 2nd day thereafter), and allografts were serially monitored for Treg infiltration, tissue oxygenation, microvascular blood flow and functional microvasculature between donor and recipients during allograft rejection. We demonstrated that C5a blocking significantly leads to enhanced presence of Tregs in the allograft, reinstates donor-recipient functional microvasculature, improves tissue oxygenation, microvascular blood flow and epithelial repair, followed by an upregulation of IL-5, TGF-β, IL-10 VEGF and ANGPT1 gene expression, while it maintained a healthy epithelium and prevented subepithelial collagen deposition at d28 post-transplantation. Together, these data indicate that inhibition of C5a signaling has potential to preserve microvasculature and rescue allograft from sustained hypoxic/ischemic phase, limits airway tissue remodeling through the induction of Treg-mediated immune-tolerance. These findings may be useful in designing anti-C5a therapy in combination with existing immunosuppressive regimens to rescue tissue/organ rejection.